Frequency and Antifungal Susceptibility of Candida Albicans and Non-albicans Candida Isolates from Diabetic Foot Ulcer at Tertiary Care Hospitals of Peshawar - Ali, Haider; Khaliq, Sehar; Ali, Bushra; Ali, Nimra; Ahmad Abbassi, Shahid (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To study the frequency and antifungal susceptibility of the Candida albicans and non-albican species in diabetic foot infections from samples collected in a tertiary care hospital of district Peshawar. METHODOLOGY: This cross-sectional study was conducted from March 2020 to February 2021 in Khyber Teaching Hospital and Hayatabad Medical Complex, Peshawar. Specimen for culture swabs or tissue from diabetic foot ulcers was taken using aseptic methods. If pus was absent in the wound, ulcer scraping was collected. One tissue sample was soaked in 10% KOH for microscopy, while the second sample was used for fungal culture and sensitivity using Sabouraud dextrose agar. RESULTS: Of the 600 samples, 200 patients had diabetic foot ulcers with positive fungal culture from Males 102(51%) and Females 98(49%). The age range was 40-78 years. The frequency of C. albicans, C. dubliniensis, C. famata, C. glabrata, C. parapsilosis, and C. lusitaniae was 23(11.5%), 27(13.5%), 19(9.5%), 19(9.5%), 88(44%) and 24(12%). C. albicans was the most common fungal species. Antifungal susceptibility testing was done, and resistance to drugs like Amphotericin, Caspofungin, Fluconazole, Flucytosine, Itraconazole, Micafungin, Voriconazole which was 6.5%, 16%, 25.5%, 5.5%, 3%, 22.5%, 21% respectively. Resistance to Fluconazole, Micafungin and Voriconazole was the highest among all commonly used antifungal drugs. CONCLUSION: Fungal infection in diabetic foot ulcers usually does not respond to antibiotics. Candia albicans and non-albicans spp are also associated with diabetic foot ulcer infection and inflammation, and these fungi have the highest resistance to commonly used antifungal agents.